Darīce ẕihn ke : bāqiyāt-i Nis̲ār Iṭāvī - Nis̲ār Iṭāvī, 1914-1974 (Shuʻbah-yi Fārsī, ʻArabī va Urdū, Em.Es. Yūnivarsiṭī āf Baṛodah : copies can be had from, University Publications Sales Unit, 1981)
Includes an editorial introduction.